2000
DOI: 10.1128/aem.66.6.2414-2421.2000
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Permeating and Nonpermeating Solutes on the Fatty Acid Composition of Pseudomonas putida

Abstract: We examined the effect of reduced water availability on the fatty acid composition of Pseudomonas putida strain mt-2 grown in a defined medium in which the water potential was lowered with the permeating solutes NaCl or polyethylene glycol (PEG) with a molecular weight of 200 (PEG 200) or the nonpermeating solute PEG 8000. Transmission electron microscopy showed that ؊1.0-MPa PEG 8000-treated cells had convoluted outer membranes, whereas ؊1.0-MPa NaCl-treated or control cells did not. At the range of water pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
83
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 50 publications
0
83
1
Order By: Relevance
“…In order to visualize unsaturated biofilms, we tagged P. putida mt-2 with the green fluorescent protein by transferring a stable, broad-host-range plasmid pPROBE-KT (18) containing the gfp gene fused to the constitutive neomycin-phosphotransferase (P nptII ) promoter. We used a permeating solute (NaCl, KCl, sucrose, polyethylene glycol 200 [PEG 200; i.e., a PEG with a molecular weight of 200]) and a nonpermeating solute (PEG 8000) to simulate the solute and matric components of the soil water potential, respectively, as described previously (11,12). Bacteria were cultivated on 50%-strength Luria-Bertani solid medium without NaCl and amended with (per liter) 1 g of MgSO 4 ⅐ 7H 2 O, 1.38 g of KH 2 PO 4 , 0.2 g of calcofluor white (Sigma Chemical Co., St. Louis, Mo.…”
mentioning
confidence: 99%
“…In order to visualize unsaturated biofilms, we tagged P. putida mt-2 with the green fluorescent protein by transferring a stable, broad-host-range plasmid pPROBE-KT (18) containing the gfp gene fused to the constitutive neomycin-phosphotransferase (P nptII ) promoter. We used a permeating solute (NaCl, KCl, sucrose, polyethylene glycol 200 [PEG 200; i.e., a PEG with a molecular weight of 200]) and a nonpermeating solute (PEG 8000) to simulate the solute and matric components of the soil water potential, respectively, as described previously (11,12). Bacteria were cultivated on 50%-strength Luria-Bertani solid medium without NaCl and amended with (per liter) 1 g of MgSO 4 ⅐ 7H 2 O, 1.38 g of KH 2 PO 4 , 0.2 g of calcofluor white (Sigma Chemical Co., St. Louis, Mo.…”
mentioning
confidence: 99%
“…In this study, many wdc loci identified were differentially regulated by solute and matric stress, although some genes were induced by both stresses. This result suggests that when the stresses are thermodynamically equivalent, cells are differently affected by each form of reduced water availability (66,67,124), and hence they employ different adaptive responses to matric and solute stresses.…”
Section: Bacterial Adaptive Mechanisms To Reduced Water Availabilitymentioning
confidence: 90%
“…From a bacterial perspective, the major difference between these two stresses is that with an osmotic stress microbes are bathed in water of diminished activity, whereas with a matric stress microbes become dehydrated by the physical removal of water from their environment and the availability of the remaining water is reduced through its sorptive interaction with soil constituents (66). In fact, as soils dry the matric potential becomes the predominant component contributing to the total water potential (67,115).…”
Section: Microbial Water Availability In Microbial Habitatsmentioning
confidence: 99%
See 2 more Smart Citations